2021
DOI: 10.1002/lio2.630
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and hearing prognosis of idiopathic sudden sensorineural hearing loss in patients undergoing hemodialysis: A retrospective study

Abstract: Background: Patients undergoing hemodialysis (HD) tend to experience hearing loss, including idiopathic sudden sensorineural hearing loss (ISSHL). However, little is known about the relationship between HD and ISSHL.Objective: To investigate the effects of HD on the hearing level and the treatment prognosis of ISSHL. Methods: We reviewed the medical records of 23 patients with ISSHL receiving HD treatment (HD group) and 101 patients with ISSHL not receiving HD treatment (non-HD group), and assessed clinical fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…However, in their cases, the initial hearing threshold was relatively lower and the age group was considerably younger compared to those in other studies, which likely contributed to their favorable outcomes. In a similar study conducted by Yamamoto et al 20 , no statistically significant differences were observed in the pretreatment hearing level and recovery of the affected ear between the HD and non-HD groups ( P = 0.12). However, a limitation of this study was the inclusion of a higher number of patients with diabetes compared to those included in the control group, which could have potentially acted as a confounding variable 21 .…”
Section: Discussionmentioning
confidence: 51%
“…However, in their cases, the initial hearing threshold was relatively lower and the age group was considerably younger compared to those in other studies, which likely contributed to their favorable outcomes. In a similar study conducted by Yamamoto et al 20 , no statistically significant differences were observed in the pretreatment hearing level and recovery of the affected ear between the HD and non-HD groups ( P = 0.12). However, a limitation of this study was the inclusion of a higher number of patients with diabetes compared to those included in the control group, which could have potentially acted as a confounding variable 21 .…”
Section: Discussionmentioning
confidence: 51%
“…However, it should be noted that in their cases, the initial hearing threshold was relatively lower and the age group was considerably younger compared to that in other studies, which likely contributed to their favorable outcomes. In a similar study conducted by Yamamoto et al [17] , no statistically signi cant differences were observed in the pre-treatment hearing level and recovery of the affected ear between the HD and non-HD groups (P = 0.12). However, it is important to note that a limitation of this study was the inclusion of a higher number of patients with diabetes compared to the control group, which could have potentially acted as a confounding variable [18] .…”
Section: Discussionmentioning
confidence: 51%
“…22 The results of this study were similar to those of Vilayur's study, as cited by Yamamoto et al, who found that the prevalence of CKD in those aged 50-59 years was 4.2% and increased to 52.2% at the age of 80-99 years. 24 In this study, the age was limited to 60 years to avoid prebiacusis bias, so we could not observe the prevalence at those over 60 years of age. Gabr et al's study found no statistically significant difference between groups of normal people, CKD patients with or without hemodialysis based on sex and age with p>0.01.…”
Section: Articlementioning
confidence: 99%